GENETIC ANALYSIS OF RESISTANCE TO BACTERIAL BLIGHT IN RICE (Oryza sativa L.) - M. Ijaz; F. A. Faiz; M.K. Bhatti.; T. H. Awan; M. Anwar; M. Ahmad; G. S. Khush (Journal of Animal and Plant Sciences, 2008)
Twenty eight resistant rice cultivars were studied for the inheritance of resistance to bacterial blight using Philippines races of Xanthomonas oryzae pv. oryzae. Results revealed that twenty six cultivars have two recessive genes for resistance. One of these governs resistance to race 1 (PXO 61) while the other gene confers resistance to race 6 (PXO 99). One cultivar Pankiraj has three recessive genes for resistance, two of that convey resistance to race 1 and while third gene conveys resistance to race 6. Another cultivar Kalonchi has one dominant and one recessive gene for resistance to race 1 and another recessive gene for resistance to Race 6. Allelism test with Xa4 and xa5 showed that the dominant and recessive gene of Kalonchi that confer resistance to race 1 are allelic to Xa4 and xa5 respectively. Similarly one of the recessive gene of Pankiraj and single recessive genes conferring resistance to race 1 in 22 cultivars are allelic to xa5. Whereas the single recessive gene for resistance to race 1 in cultivar Bazail 408, Kaun Kaek, Phcar Tien P65 and Aus 364 are different and segregate independently of xa5. Similarly allele test with xa13 and xa24 showed that single recessive gene conferring resistance to race 6 in Aus 364 is allelic to xa13. All the others 27 cultivars have single recessive gene for resistance to race 6 are non allelic to xa13 and xa24 and hence are new genes. Molecular analysis of the cultivars using STS marker for xa5 and xa13 confirmed most of the results (presence of new genes) obtained from genetic analysis.
Keywords: Inheritance; Resistance; Allelism; Cultivars; Rice.